1995
DOI: 10.3109/00365519509110257
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the release and turnover of a human neutrophil lipocalin

Abstract: A 24-kDa protein was purified from human neutrophil extracts and shown to be the newly discovered neutrophil gelatinase-associated lipocalin (NGAL), based on structural and immunochemical data. A specific enzyme-linked immunosorbent assay (ELISA) was developed for the determination of NGAL in human plasma and tissue fluids. Normal human plasma contains 72 micrograms l-1 of NGAL (range 40-109 micrograms l-1) in two main forms, monomer and dimer. 35S-methionine metabolic studies of human neutrophils showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 18 publications
3
95
0
1
Order By: Relevance
“…1 NGAL has short half-life, estimated at 10-20 min due to rapid elimination from circulation by the kidney. 3 It is postulated that increased serum NGAL (sNGAL) and urinary NGAL (uNGAL) is a sensitive marker of acute kidney injury (AKI), predominantly of tubular cell damage, not related to glomerular filtration decline. 4,5 Additionally, it was shown that NGAL is a marker of neutrophil activation and the severity of sepsis in populations other than newborns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 NGAL has short half-life, estimated at 10-20 min due to rapid elimination from circulation by the kidney. 3 It is postulated that increased serum NGAL (sNGAL) and urinary NGAL (uNGAL) is a sensitive marker of acute kidney injury (AKI), predominantly of tubular cell damage, not related to glomerular filtration decline. 4,5 Additionally, it was shown that NGAL is a marker of neutrophil activation and the severity of sepsis in populations other than newborns.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The major biological role of this 24 kDa protein is iron-chelating, preventing its uptake by microorganisms. 1 NGAL has short half-life, estimated at 10-20 min due to rapid elimination from circulation by the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a limited number of studies investigating the value of NGAL on acute infections. In the study conducted by Axelsson et al it was seen that serum NGAL level was 10 times higher in patients with acute peritonitis compared to control group [18]. In another study carried out by Chakraborty et al serum NGAL levels were higher in patients with acute pancreatitis in relation to severity of the disease [9].…”
Section: Discussionmentioning
confidence: 85%
“…As IL-8 stimulates from human neutrophils [22] the release of NGAL [23] and MMP-9 [25,26] affecting coagulation [14,15], the observed IL-8 increase suggests that this factor may be involved in facilitating the coagulation process.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to remember that IL-8 exhibits the capacity to recruit the neutrophils [22] that releases NGAL [23], sorted to azurophil granules [24]. In addition, as IL-8 stimulates from human neutrophils [22] the release of NGAL [23] and MMP-9 [25,26] affecting coagulation [14,15], the IL-8 increase, observed, suggest that this factor may facilitate the coagulation process. High values of IL-8 or other chemokines can be used to predict cardiovascular risk [27], and indicate a probable future CAD in normal subjects [28,29].…”
Section: Discussionmentioning
confidence: 99%